Bagasse waste-free dissociation method and application thereof

Through the hydrothermal reaction between bagasse and boric acid, high-efficiency carbon materials for contaminated water treatment and zinc ion buckle batteries were prepared, which solved the problems of low resource utilization efficiency and environmental pollution in bagasse treatment, and realized multifunctional applications and High-efficiency pollutant degradation and electrochemical performance improvement.

CN119191260APending Publication Date: 2024-12-27WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411283381.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sugar cane bagasse treatment technology has problems such as low calorific value, environmental pollution, waste of resources and low utilization efficiency, and the traditional catalysts have poor stability and poor electrochemical performance.

Method used

By hydrothermal reaction with sugarcane bagasse and boric acid, carbon microspheres supported by manganese and cobalt bimetals and carbon materials supported by boron and nitrogen are obtained. They are used for contaminated water treatment and zinc ion buckle batteries, achieving efficient degradation of pollutants and excellent respectively electrochemical properties.

Benefits of technology

The all-round utilization of sugarcane bagasse is achieved, high specific surface area catalysts and excellent electrochemical performance materials are obtained, and the insufficient performance of contaminated water treatment and zinc ion buckle batteries is solved, and resource utilization and environmental friendliness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005042356930000011
    Figure HDA0005042356930000011
  • Figure HDA0005042356930000012
    Figure HDA0005042356930000012
  • Figure HDA0005042356930000013
    Figure HDA0005042356930000013
Patent Text Reader

Abstract

The invention discloses a bagasse non-waste dissociation method which comprises the following steps: adding bagasse and boric acid into water for hydrothermal reaction, then filtering and collecting filtrate A and filter residue B; adding melamine, manganese chloride and cobalt chloride into the filtrate A, then carrying out hydrothermal reaction to realize double doping of manganese and cobalt, and then carrying out carbonization treatment to obtain a manganese-cobalt bimetal loaded carbon microsphere material which is applied to degradation of antibiotic wastewater; treating the filter residue B with hydrogen peroxide to obtain lignin microspheres and delignified filter residue C; and doping boron and nitrogen into the filter residue C, and carbonizing to obtain the carbon positive electrode material of the zinc ion button cell. According to the method, grading and comprehensive utilization of the bagasse are fully achieved, two carbon materials are obtained while the lignin microspheres are obtained, the two carbon materials are used for polluted water treatment and zinc ion button cells respectively, and the excellent pollutant degradation effect and electrochemical performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomass materials and water treatment, and more specifically, to a method for waste-free separation of bagasse and application thereof. Background Art

[0002] Bagasse is the main waste of China's sugar industry (accounting for 30%-35%), and is also a very important renewable biomass resource. It is mainly composed of cellulose (accounting for 40%-50%), hemicellulose (accounting for 20%-30%), and lignin (accounting for 15%-20%). Hemicellulose, as a natural polysaccharide, is between cellulose and lignin, while lignin has a network structure that serves as a supporting skeleton to surround and reinforce cellulose. Bagasse is widely available, inexpensive, and has great energy potential.

[0003] However, at present, most of the sugarcane bagasse in my country is converted into biogas or biomass fuel through fermentation, anaerobic digestion and other technologies, and some of it becomes organic fertilizer after composting. However, as a biomass fuel, sugarcane bagasse has problems such as low calorific value; as an organic fertilizer, there will also be a series of problems such as environmental pollution, heavy metal pollution, material waste, large volume, and low fertilizer efficiency during the composting process. Simple incineration or composting treatment makes the utilization efficiency of sugarcane bagasse low and there is a risk of secondary pollution, resulting in resource waste and environmental damage. The method for treating sugarcane bagasse provided by the present invention can effectively overcome the above problems. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for waste-free separation of sugarcane bagasse in view of the deficiencies in the above-mentioned prior art, which fully realizes the classification and all-round utilization of sugarcane bagasse, and while obtaining lignin microspheres, two kinds of carbon materials can also be obtained, which are used for polluted water treatment and zinc ion button batteries respectively, and have excellent pollutant degradation effects and electrochemical properties.

[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0006] A method for waste-free separation of bagasse comprises the following steps:

[0007] (1) Add bagasse and boric acid to solvent water, stir evenly, perform hydrothermal reaction in a reactor, and then filter to obtain filtrate A and residue B.

[0008] (2) adding melamine, manganese chloride and cobalt chloride to the filtrate A obtained in step (1), stirring evenly, and then performing a hydrothermal reaction to achieve dual doping of manganese and cobalt. After the reaction is completed, collecting the solid, drying it and transferring it to a tubular furnace for carbonization treatment to obtain a manganese-cobalt bimetallic loaded carbon microsphere material (Mn-Co-C carbon microsphere material).

[0009] (3) The filter residue B obtained in step (1) is treated with hydrogen peroxide to obtain lignin microspheres and delignified filter residue C, respectively.

[0010] (4) The delignified filter residue C obtained in step (3) is loaded with boron and nitrogen non-metals and then carbonized to obtain a boron and nitrogen loaded carbon material.

[0011] According to the above scheme, in step (1), the concentrations of bagasse and boric acid in solvent water are both 25-75 g / L, and the stirring time is generally 0.4-1 h; the temperature of the hydrothermal reaction is 160-200° C., and the time is 0.5-1 h.

[0012] According to the above scheme, in step (2), the concentrations of melamine, manganese chloride and cobalt chloride in filtrate A are all 10-30 g / L; the temperature of the hydrothermal reaction is 160-200° C., and the time is 8-15 h.

[0013] According to the above scheme, in step (2), the temperature of the carbonization treatment is 700-850°C and the time is 1-3 hours. Furthermore, when the carbonization treatment is carried out in a tubular furnace, the temperature is increased to the carbonization treatment temperature at a heating rate of 5-10°C / min.

[0014] According to the above scheme, the specific process of step (3) is: stirring the filter residue B in hydrogen peroxide for 2-4 hours, during which the temperature is controlled at 70-90°C, and then filtering to obtain a filtrate D and a delignified filter residue C; then, adjusting the pH of the filtrate D to 5.5-6.0 with HCl, then adding a large amount of ethanol (the volume of ethanol is 2-4 times the volume of the filtrate D), standing overnight and then evaporating the ethanol, then adjusting the pH to 2.0-2.5 with HCl, and finally centrifuging to obtain lignin.

[0015] According to the above scheme, the lignin obtained in step (3) can be further treated to obtain lignin microspheres (LNP). Specifically, the lignin is dispersed in a mixed solvent of tetrahydrofuran and deionized water, and subjected to a solvent thermal treatment to obtain LNP. The concentration of lignin in the mixed solvent is 1-3 g / L, the volume ratio of tetrahydrofuran to deionized water is 1:(3-5), the temperature of the solvent thermal reaction is 150-180°C, and the time is 10-15h.

[0016] According to the above scheme, the process of step (4) is as follows: the filter residue C and KCl are mixed in solvent water (the concentrations of the filter residue C and KCl in the solvent water are 10-30 g / L and 50-150 g / L, respectively), and then stirred at 90-100° C. for 0.4-1 h, and then cooled to 50-80° C., and then appropriate amounts of urea, KHCO3 and boric acid solution are added (the amounts of urea and KHCO3 added are based on the concentrations of 10-30 g / L and 50-150 g / L, respectively, in the solvent water in this step); g / L, 50-80g / L, the volume ratio of the boric acid solution to the solvent water in this step is 1: (4-6), the concentration of the boric acid solution itself is 60-100g / L), then stirred at 50-80°C for 0.5-1h, freeze-dried after cooling, and finally carbonized in a tubular furnace, the carbonization temperature is 650-750°C, the time is 1.5-4h, and the heating rate is 4-10°C / min to obtain a boron-nitrogen loaded carbon material (BNC material). Among them, KCl acts as a catalyst to increase the chemical reaction rate by reducing the activation energy; KHCO3 acts as a hole sacrificial agent, which can provide holes during the reaction process, thereby accelerating the reaction rate.

[0017] The manganese-cobalt bimetallic loaded carbon microsphere material (Mn-Co-C carbon microsphere material) obtained by the above method can be used to degrade pollutants in water bodies. The specific application method is: the Mn-Co-C carbon microsphere material (as a catalyst) and potassium peroxymonosulfate salt (as an activator) are added to the polluted water body at the same time, thereby achieving the degradation of pollutants in the water body. Among them, the addition concentration of the Mn-Co-C carbon microsphere material in the water body is 0.05-0.5g / L, and the addition concentration of the activator in the water body is 0.5-2mM.

[0018] The boron-nitrogen loaded carbon material obtained by the above method is used as the positive electrode of a zinc ion button battery. The specific application method is: the carbon material is mixed with a conductive agent and a binder solvent (such as 1-methyl-2-pyrrolidone (NMP)) and then evenly coated on an aluminum foil as the positive electrode, a zinc sheet as the negative electrode, and a zinc sulfate solution as the electrolyte to assemble a zinc ion button battery.

[0019] The present invention uses bagasse as a carbon source, and after grading the bagasse, lignin microspheres are obtained, and two carbon materials can also be obtained, which are used for water treatment and zinc ion button batteries respectively. Compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects:

[0020] (1) The manganese-cobalt bimetallic loaded carbon microsphere material obtained by the present invention has a high specific surface area and a large number of catalytic active sites, which solves many problems of poor stability, difficult recovery, high energy consumption, high cost, etc. of traditional catalysts. Through the synergistic modification of manganese-cobalt bimetallic, potassium peroxymonosulfate salt is efficiently activated to rapidly degrade organic pollutants in water.

[0021] (2) Compared with pure carbon-based materials, the boron-nitrogen loaded carbon material obtained by the present invention has excellent electrochemical properties and can be used in zinc ion button batteries. The assembled zinc ion button battery provides excellent specific capacitance at a current density of 1A / g and has high power density and energy density.

[0022] (3) The present invention can also extract lignin, and can further process to obtain lignin microspheres (LNP), which are non-toxic, harmless, green and environmentally friendly.

[0023] (4) The boron-nitrogen loaded carbon material prepared by the present invention is environmentally friendly. Its application in zinc ion button batteries can alleviate the dilemma of battery recycling to a certain extent, is beneficial to environmental protection, and also solves the problem of low energy density and power density of energy storage materials.

[0024] In summary, the present invention utilizes raw materials to the greatest extent possible, utilizes the filter residue and filtrate of the raw materials in an all-round way, dissociates the bagasse without waste, and realizes multifunctional applications in different fields such as lignin microspheres (LNP), water treatment (such as antibiotic degradation), and energy storage devices (zinc ion button batteries) after full classification. It has very significant resource and environmental value, achieves the coordinated development and maximum benefit of materials, environment and energy, and solves the current limitations in the application of bagasse. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image (SEM) of the Mn-Co-C carbon microsphere material prepared in Example 1.

[0026] Figure 2 This is the X-ray photoelectron spectroscopy analysis chart (XPS) of the Mn-Co-C carbon microsphere material prepared in Example 1.

[0027] Figure 3 When the Mn-Co-C carbon microsphere material prepared in Example 1 degrades tetracycline drugs under different pH conditions,

[0028] Changes in tetracycline drug concentration over time.

[0029] Figure 4 is a scanning electron microscope image (SEM) of the LNP prepared in Example 1.

[0030] Figure 5 3 is a scanning electron microscope image (SEM) of the BNC carbon material prepared in Example 1.

[0031] Figure 6 This is the Raman spectrum (Raman) of the BNC carbon material prepared in Example 1.

[0032] Figure 7 This is the battery cycle curve of the assembled zinc ion button battery of the BNC carbon material prepared in Example 1. DETAILED DESCRIPTION

[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0034] Example 1

[0035] A method for the waste-free separation of bagasse, comprising the following steps:

[0036] (1) 5 g of bagasse and 5 g of boric acid were added to 100 mL of deionized water, stirred for 30 min, reacted in a hydrothermal reactor at 180 °C for 1 h, and then filtered to obtain a filtrate A and a residue B.

[0037] (2) Add 2 g of melamine, 2 g of manganese chloride and 2 g of cobalt chloride to the filtrate A (about 100 mL) obtained in step (1), stir for 30 min, react in a hydrothermal reactor at 180° C. for 12 h to achieve manganese and cobalt element doping, and then filter to obtain a solid; dry the solid in a blast drying oven, transfer it to a tubular furnace for carbonization, heat it to a carbonization temperature of 800° C. at a heating rate of 5° C. / min, and carbonize it for 2 h to obtain a manganese-cobalt bimetallic loaded carbon microsphere material (Mn-Co-C carbon microsphere material).

[0038] (3) The filter residue B (about 5 g) obtained in step (1) was stirred in 100 mL of hydrogen peroxide solvent for 3 h, during which the temperature was controlled at 80° C., and then filtered to obtain filtrate D and filter residue C; the pH of the filtrate D was adjusted to 5.5-6.0 with HCl, and then a large amount of ethanol (the volume was 3 times the volume of the filtrate D) was added. After standing overnight, the ethanol was evaporated, and then the pH was adjusted to 2.0-2.5 with HCl, and finally lignin (about 1 g) was centrifuged.

[0039] (4) About 1 g of lignin obtained in step (3) was dissolved in 100 mL of tetrahydrofuran, and then 400 mL of deionized water was added and stirred for 12 h. Finally, the mixture was reacted at 160° C. for 12 h in a hydrothermal reactor and centrifuged to obtain LNP.

[0040] (5) Take 1 g of the filter residue C obtained in step (3) and mix it with 5 g of KCl and disperse it in 50 mL of deionized water, then stir it at 90 ° C for 0.5 h, cool it to 60 ° C, add 1 g of urea and 3 g of KHCO3, then add 10 mL of boric acid solution (80 mg / mL), continue to stir at 60 ° C for 0.5 h, cool it and freeze-dry it, and finally carbonize it in a tubular furnace, raise the temperature to 700 ° C at a heating rate of 5 ° C / min, and carbonize it for 2 h to obtain a boron and nitrogen loaded carbon material (BNC material).

[0041] Depend on Figure 1 and Figure 2 It can be seen that manganese and cobalt are loaded on the spherical body respectively, and the XPS analysis of electron binding energy can also indicate that the manganese-cobalt bimetal is successfully loaded.

[0042] Depend on Figure 4 It can be seen that: through the observation of scanning electron microscope, it was found that lignin was spherical after heat exchange with tetrahydrofuran solvent, indicating that lignin was successfully prepared into LNP.

[0043] Depend on Figure 5 and Figure 6 It can be seen that: through observation under a scanning electron microscope, the pore size and specific surface area of ​​the BNC material are very large, and there are many channels. The Raman spectrum also reflects that its degree of graphitization is very high.

[0044] Application Example 1

[0045] (1) A tetracycline solution was used as the water body, with a concentration of 20 mg / L (i.e. 20 ppm), a pH value of 2-3.5, a controlled catalyst concentration of 0.1 g / L, and an activator concentration of 1.5 mM. Figure 3 As shown, when the Mn-Co-C carbon microsphere material degrades tetracycline under different pH conditions, the concentration of tetracycline drug gradually decreases with time, confirming that the Mn-Co-C carbon microsphere material has a high response to tetracycline in a wider pH range.

[0046] (2) The Mn-Co-C carbon microsphere material prepared in Example 1 is used to remove tetracycline from water. The specific process is as follows: potassium peroxymonosulfate and the Mn-Co-C carbon microsphere material (catalyst) prepared in Example 1 are added to a 20 mg / L tetracycline solution, and the concentrations of potassium peroxymonosulfate and Mn-Co-C carbon microsphere material in the solution are controlled to be 1.5 mM and 0.1 g / L, respectively. Then, the solution is oscillated in a water bath at a constant temperature of 25°C. After 30 minutes of degradation reaction, a tetracycline removal rate of 93.8% can be achieved.

[0047] Application Example 2

[0048] Figure 7The figure is a cycle diagram of the zinc ion button battery assembled with the BNC carbon material prepared in Example 1. The catalyst (BNC carbon material), conductive agent (carbon black) and binder (PVDF) were mixed with 1-methyl-2-pyrrolidone (NMP) in a mass ratio of 8:1:1, and then evenly coated on aluminum foil as the positive electrode, and zinc sheet was used as the negative electrode, 1M zinc sulfate solution was used as the electrolyte, and the zinc ion button battery was assembled. The battery cycle curve is shown in FIG. Figure 7 As shown, the capacity retention rate is close to 100% after 10,000 cycles at high current density, and the Coulombic efficiency is also very high, confirming that the assembled zinc ion button battery has a stable operating voltage, high battery capacity and long life.

[0049] After the zinc ion button cell was left to stand overnight, its electrochemical performance was tested using an electrochemical workstation. The button cell provided an excellent specific capacitance of 346F / g at a current density of 1A / g, and an energy density of up to 212Wh / kg when the power density was 1048W / kg.

[0050] Application Example 3

[0051] 1.5 mM potassium peroxymonosulfate and 2.5 mg of the catalyst prepared in Example 1 were added to a 20 mg / L (ie, 20 ppm) tetracycline solution. Then, under the same experimental conditions, a 91.7% tetracycline removal rate was achieved after a 30-minute degradation reaction.

[0052] Application Example 4

[0053] Potassium peroxymonosulfate and the Mn-Co-C carbon microsphere material (catalyst) prepared in Example 1 were added to a 20 mg / L (i.e., 20 ppm) tetracycline solution, and the concentrations of potassium peroxymonosulfate and Mn-Co-C carbon microsphere material in the solution were controlled to be 1 mM and 0.1 g / L, respectively. The solution was then oscillated in a water bath at a constant temperature of 25° C., and the degradation reaction was completed after 30 minutes, and a tetracycline removal rate of 84.8% was achieved.

[0054] Application Example 5

[0055] The difference between the zinc ion button cell and application example 2 is that the mass ratio of the catalyst conductive agent to the binder is 6:2:2. After the zinc ion button cell is assembled, it is left to stand overnight and its electrochemical performance is tested using an electrochemical workstation. The button cell provides an excellent specific capacitance of 321F / g at a current density of 1A / g, and an energy density of up to 198Wh / kg at a power density of 1100W / kg.

[0056] Application Example 6

[0057] The difference between the zinc ion button cell and application example 2 is that the mass ratio of the catalyst conductive agent to the binder is 7:2:1. After the zinc ion button cell is assembled, it is left to stand overnight and its electrochemical performance is tested using an electrochemical workstation. The button cell provides an excellent specific capacitance of 315F / g at a current density of 1A / g, and an energy density of up to 185Wh / kg when the power density is 1020W / kg.

[0058] For those skilled in the art, the above description is only a preferred embodiment of the present invention. Any changes, equivalent replacements, etc. made within the spirit and principle of the present invention are within the protection scope of the present invention.

Claims

1. A method for the waste-free separation of bagasse, characterized in that: The following steps are involved: (1) mixing bagasse, boric acid and solvent water, performing a hydrothermal reaction in a reactor, and then filtering to obtain a filtrate A and a residue B; (2) adding melamine, manganese chloride and cobalt chloride to the filtrate A obtained in step (1), mixing, and then performing a hydrothermal reaction to achieve dual doping of manganese and cobalt. After the reaction is completed, collecting the solid, drying it, and transferring it to a tubular furnace for carbonization treatment to obtain a manganese-cobalt bimetallic loaded carbon microsphere material; (3) treating the filter residue B obtained in step (1) with hydrogen peroxide to obtain lignin microspheres and delignified filter residue C; (4) The delignified filter residue C obtained in step (3) is loaded with boron and nitrogen non-metals and then carbonized to obtain a boron and nitrogen loaded carbon material.

2. The method for waste-free separation of bagasse according to claim 1, characterized in that: In step (1), the concentrations of bagasse and boric acid in solvent water are both 25-75 g / L; the temperature of the hydrothermal reaction is 160-200° C., and the time is 0.5-1 h.

3. The method for waste-free separation of bagasse according to claim 1, characterized in that: In step (2), the concentrations of melamine, manganese chloride and cobalt chloride in filtrate A are all 10-30 g / L; the temperature of the hydrothermal reaction is 160-200° C., and the time is 8-15 h.

4. The method for waste-free separation of bagasse according to claim 1, characterized in that: In step (2), the temperature of the carbonization treatment is 700-850°C and the time is 1-3h.

5. The method for waste-free separation of bagasse according to claim 1, characterized in that: In step (2), when the carbonization treatment is carried out in a tubular furnace, the temperature is increased to the carbonization treatment temperature at a heating rate of 5-10°C / min.

6. The method for waste-free separation of bagasse according to claim 1, characterized in that: The specific process of step (3) is as follows: stirring the filter residue B in hydrogen peroxide for 2-4 hours, during which the temperature is controlled at 70-90° C., and then filtering to obtain a filtrate D and a delignified filter residue C; then, adjusting the pH of the filtrate D to 5.5-6.0 with hydrochloric acid, and then adding ethanol 2-4 times the volume of the filtrate D, standing overnight and then evaporating the ethanol, then adjusting the pH to 2.0-2.5 with hydrochloric acid, and finally centrifuging to obtain lignin.

7. The method for waste-free separation of bagasse according to claim 6, characterized in that: The lignin obtained in step (3) is dispersed in a mixed solvent of tetrahydrofuran and water, and subjected to solvent thermal treatment to obtain lignin microspheres; wherein the concentration of lignin in the mixed solvent is 1-3 g / L, the volume ratio of tetrahydrofuran to water is 1:(3-5), the temperature of the solvent thermal reaction is 150-180° C., and the time is 10-15 h.

8. The method for waste-free separation of bagasse according to claim 1, characterized in that: The specific process of step (4) is as follows: the filter residue C and KCl are mixed in solvent water, and then stirred evenly at 90-100°C, and when cooled to 50-80°C, an appropriate amount of urea, KHCO3 and boric acid solution are added, and then stirred evenly at 50-80°C, and freeze-dried after cooling, and finally carbonized in a tubular furnace, the carbonization temperature is 650-750°C, and the time is 1.5-4h to obtain a boron-nitrogen loaded carbon material; wherein the addition concentrations of the filter residue C and KCl in the solvent water are 10-30g / L and 50-150g / L, respectively, the addition concentrations of urea and KHCO3 in the solvent water are 10-30g / L and 50-80g / L, respectively, the volume ratio of the boric acid solution to water is 1:(4-6), and the concentration of the boric acid solution itself is 60-100g / L.

9. The use of the manganese-cobalt bimetallic loaded carbon microsphere material prepared by the method of claim 1 for degrading pollutants in water, characterized in that: The specific application method is: adding the manganese-cobalt bimetallic loaded carbon microsphere material as a catalyst and an activator potassium peroxymonosulfate into the polluted water body at the same time to achieve the degradation of pollutants in the water body; wherein, the manganese-cobalt bimetallic loaded carbon microsphere material is added to the water body at a concentration of 0.05-0.5g / L, and the activator is added to the water body at a concentration of 0.5-2mM.

10. Use of the boron-nitrogen loaded carbon material prepared by the method of claim 1 as a positive electrode of a zinc ion button battery, characterized in that: The specific application method is: the boron nitrogen loaded carbon material is mixed with a conductive agent and a binder with a solvent and then evenly coated on an aluminum foil as a positive electrode, a zinc sheet as a negative electrode, and a zinc sulfate solution as an electrolyte to assemble a zinc ion button battery.